1988
DOI: 10.1083/jcb.106.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization and biosynthesis of secreted and cytoplasmic forms of gelsolin

Abstract: Abstract. Gelsolin is an actin regulatory protein which is unique among vertebrates in that it is found as both an intrinsic cytoplasmic protein and as a secreted plasma protein. We demonstrate that plasma and cytoplasmic gelsolins are derived by alternative transcriptional initiation sites and message processing from a single gene 70 kb long, containing at least 14 exons. Their message and amino acid sequences are identical except at the 5' end/NH2 termini. The cytoplasmic-specific 5' sequence is derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 41 publications
4
83
1
Order By: Relevance
“…We first carried out direct sequencing of the gelsolin promoter (from Ϫ580 to 75, relative to the transcription start site) using the PCR products derived from human bladder cancer cells (DAB-1, KU-7 and UMUC-2) and the cells derived from normal uroepithelium (SV-HUC-1). Although it was found that the gelsolin promoter of cancer and normal tissue-derived cells were identical in sequence, this sequence differed from that previously reported at 2 nucleotide positions: Ϫ153 G (from K, which shows G or T in the original report 24 ) and Ϫ170 T (our addition) from the transcription start site (Fig. 1).…”
Section: Mutation and Methylationcontrasting
confidence: 76%
“…We first carried out direct sequencing of the gelsolin promoter (from Ϫ580 to 75, relative to the transcription start site) using the PCR products derived from human bladder cancer cells (DAB-1, KU-7 and UMUC-2) and the cells derived from normal uroepithelium (SV-HUC-1). Although it was found that the gelsolin promoter of cancer and normal tissue-derived cells were identical in sequence, this sequence differed from that previously reported at 2 nucleotide positions: Ϫ153 G (from K, which shows G or T in the original report 24 ) and Ϫ170 T (our addition) from the transcription start site (Fig. 1).…”
Section: Mutation and Methylationcontrasting
confidence: 76%
“…Gelsolin segment 5 (amino acid sequence 516-618), segment 5-6 (amino acid sequence 516-731) and segment 6 (amino acid sequence 640-731) [15,16,29] were obtained by PCR amplification with LKCG as a template. Each PCR product was subcloned into the LK444 expression plasmid (a kind gift from P. Gunning) [13,20] after insertion of a FLAG tag sequence at the 5' termini or into EcoRI-XhoI site of pCMV-FLAG expression plasmid which consists of pcDNA3.1(+) Invitrogen, Carlsbad, CA and 3xFLAG tag.…”
Section: Plasmids Cells and Transfectionmentioning
confidence: 99%
“…Gelsolin, an actin-regulatory protein that modulates actin assembly and disassembly, is found as both an intrinsic cytoplasmic protein and as a secreted plasma protein [15,16]. Immunocytochemical studies using anti-gelsolin antibody revealed that the protein is localized in filopodia and the body part of growth cones of neuronally differentiated rat pheochromocytoma (PC12) cells treated with nerve growth factor (NGF) [31].…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the amount of the 40-kDa earthworm actin modulator in annelid muscle [13], but significantly higher than that calculated for mammalian skeletal muscle [44, 4.51. Despite its low content in cytoplasmic gelsolin [46], mammalian muscle synthesizes relatively large amounts of the slightly different plasma gelsolin variant [24,47,48]. We assume that the purified crayfish modulator is exclusively cytoplasmic, since the protein appeared as a single component in two-dimensional electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis revealed a characteristic sixfold repeated pattern in the gelsolin-type proteins [15, 18, 211 and a threefold repeat in severin and fragmin with high similarity to one half of the gelsolin molecule [17], thus indicating that the gelsolin-like proteins may have evolved from severin-like proteins by gene duplication [16,22,231. It was initially assumed that the 80-ma-type proteins exclusively occur in vertebrates [24]. However, recent findings of a 110-kDa villin-like protein in sea urchin eggs [25] and a gelsolin-like protein in Drosophila [26] suggest a more complex situation where both types of protein may occur within the same phylum.…”
mentioning
confidence: 99%